Cationic Adsorption-Induced Microlevelling Effect: A Pathway to Dendrite-Free Zinc Anodes - Jiang, Long; Ding, Yiqing; Li, Le; Tang, Yan; Zhou, Peng; Lu, Bingan; Tian, Siyu; Zhou, Jiang (Nano-Micro Letters, 2025)
Dendrite growth represents one of the most significant challenges that impede the development of aqueous zinc-ion batteries. Herein, Gd3+ ions are introduced into conventional electrolytes as a microlevelling agent to achieve dendrite-free zinc electrodeposition. Simulation and experimental results demonstrate that these Gd3+ ions are preferentially adsorbed onto the zinc surface, which enables dendrite-free zinc anodes by activating the microlevelling effect during electrodeposition. In addition, the Gd3+ additives effectively inhibit side reactions and facilitate the desolvation of [Zn(H2O)6]2+, leading to highly reversible zinc plating/stripping. Due to these improvements, the zinc anode demonstrates a significantly prolonged cycle life of 2100 h and achieves an exceptional average Coulombic efficiency of 99.72% over 1400 cycles. More importantly, the Zn//NH4V4O10 full cell shows a high capacity retention rate of 85.6% after 1000 cycles. This work not only broadens the application of metallic cations in battery electrolytes but also provides fundamental insights into their working mechanisms. Highlights: 1 A microlevelling agent containing Gd3+ ions significantly enhances the reversibility and stability of zinc anodes. 2 Gd3+ ions are preferentially adsorbed onto zinc surface, shielding zinc deposition at protrusions. 3 Adsorbed Gd3+ ions establish a water-poor electric double layer, suppressing side reactions at the interface.